Interaction between phonemic abilities and syllable congruency effect in young readers*. Issue 2 (4th January 2012) - CHETAIL, FABIENNE; MATHEY, STÉPHANIE
ABSTRACT: This study investigated whether and to what extent phonemic abilities of young readers (Grade 5) influence syllabic effects in reading. More precisely, the syllable congruency effect was tested in the lexical decision task combined with masked priming in eleven-year-old children. Target words were preceded by a pseudo-word prime sharing the first three letters that either corresponded to the syllable (congruent condition) or not (incongruent condition). The data showed that the syllable priming effect interacted with the score of phonemic abilities. In children with good phonemic skills, word recognition was delayed in the congruent condition compared to the incongruent condition, while it was speeded up in children with weaker phonemic skills. These findings are discussed in a lexical access model including syllable units.